1998
DOI: 10.1007/s002590050320
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetry of transmission measurements in nuclear medicine: a study using anthropomorphic phantoms and thermoluminescent dosimeters

Abstract: Quantification in positron emission tomography (PET) and single photon emission tomographic (SPET) relies on attenuation correction which is generally obtained with an additional transmission measurement. Therefore, the evaluation of the radiation doses received by patients needs to include the contribution of transmission procedures in SPET (SPET-TM) and PET (PET-TM). In this work we have measured these doses for both PET-TM and SPET-TM. PET-TM was performed on an ECAT EXACT HR+ (CTI/Siemens) equipped with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 8 publications
0
14
0
5
Order By: Relevance
“…This radiation dose to the fetus represents activity from the administered radiopharmaceutical alone. Because all our studies were performed as PET-only studies with 68 Ge rod source transmission scanning for attenuation correction, the additional radiation exposure from the transmission scanning was negligible (12,13) and was not included in the dose estimates. The observed uptake and time-activity integrals from this study are compared in Table 4 with those from 2 other studies, 1 by Stabin (14), assigned on the basis of observed activity measured in primates, and 1 by Zanotti-Fregonara et al (15), measured in 1 human patient at about 10 wk of gestation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This radiation dose to the fetus represents activity from the administered radiopharmaceutical alone. Because all our studies were performed as PET-only studies with 68 Ge rod source transmission scanning for attenuation correction, the additional radiation exposure from the transmission scanning was negligible (12,13) and was not included in the dose estimates. The observed uptake and time-activity integrals from this study are compared in Table 4 with those from 2 other studies, 1 by Stabin (14), assigned on the basis of observed activity measured in primates, and 1 by Zanotti-Fregonara et al (15), measured in 1 human patient at about 10 wk of gestation.…”
Section: Resultsmentioning
confidence: 99%
“…for attenuation correction in lieu of CT. This ability facilitates further reduction in the fetal radiation exposure from 18 F-FDG PET in pregnant patients because the radiation dose from a 68 Ge rod source is negligible (12,13). Although the exact values of fetal radiation dose from transmission scanning with a 68 Ge rod source have not been calculated, for comparative purposes the effective dose from this method of scanning for cardiac and brain transmission studies has been estimated to be approximately 0.00077 and 0.00027 mSv/ MBqÁh, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Performed in a minority of nuclear cardiology laboratories, attenuation correction scans performed with either radioisotope sources or low-dose CT have Es that are small compared with those of radionuclide studies. 19,20 Table 3 demonstrates the effect of the tissue weighting factors on effective dose, using the 3 ICRP w T schema, and compares E 1 determined with the use of dose coefficients from ICRP tables with those from manufacturers' PIs. Organ doses for selected protocols are summarized in Table IV in the onlineonly Data Supplement, which lists the organs receiving the highest equivalent doses for each protocol.…”
Section: Dosimetry Of Nuclear Cardiology Studiesmentioning
confidence: 99%
“…One limitation of this approach was that the transmission data can be of poor quality; however, iterative reconstruction of the line source data significantly improves the quality of the reconstructed transmissions maps. 22,23 This approach, when sufficient counts are present, provides a very low radiation dose 24,25 with very highquality attenuation maps for SPECT and for PET using a relatively short transmission acquisition (see Figure 1). …”
Section: Line Source Attenuation Correctionmentioning
confidence: 99%